2006
DOI: 10.1017/s0265021505002036
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine myotoxicity after single intramuscular injection in rats

Abstract: Ropivacaine after single intramuscular injection caused reversible muscle damage in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…Much of the research on neurotoxicity of local anesthetics has been done in in vitro models, particularly with intrathecal application. There is evidence that nearly all local anesthetics can have myotoxic, neurotoxic, and cytotoxic effects in various tissues under certain conditions, 17,22,[29][30][31][32][33][34][35][36][37] however local anesthetics do vary in their neurotoxic potential. 16,38,39 Several studies have demonstrated that local anesthetics can lead to fragmentation of DNA and disrupt the membrane potential in mitochondria, resulting in the uncoupling of oxidative phosphorylation, which may result in apoptosis.…”
Section: Vascular Injurymentioning
confidence: 99%
“…Much of the research on neurotoxicity of local anesthetics has been done in in vitro models, particularly with intrathecal application. There is evidence that nearly all local anesthetics can have myotoxic, neurotoxic, and cytotoxic effects in various tissues under certain conditions, 17,22,[29][30][31][32][33][34][35][36][37] however local anesthetics do vary in their neurotoxic potential. 16,38,39 Several studies have demonstrated that local anesthetics can lead to fragmentation of DNA and disrupt the membrane potential in mitochondria, resulting in the uncoupling of oxidative phosphorylation, which may result in apoptosis.…”
Section: Vascular Injurymentioning
confidence: 99%
“…Acute and chronic myotoxic effects of BVC and RVC, after peripheral nerve block, were evaluated by Zink et al 23,24 Local anesthetics were administered by continuous injection for 6 hours, and muscle tissues were collected and processed after 1 hour, 7 days, and 28 days from the end of the injection, showing that RVC's myotoxic potential is more moderate than that of BVC. Amaniti et al 25 found that RVC administered in a single IM dose (at concentrations of 0.5% and 0.75%) caused dose-dependent damage in rat muscle. A combination of BVC and tetrodotoxin, a potent sodium channel blocker, administrated in rats, has been found to cause increased duration of neural blockade without a consequent increase in myotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A score of 0 to 3 was assigned for each slide: 0 = no fiber damage, 1 = localized and/or sparsely scattered fiber destruction, 2 = more extensive necrosis after major connective tissue planes and involving numerous muscle fascicles, and 3 = destruction of essentially the entire muscle mass in the eye-field. [22][23][24][25] The images were codified and 2 individuals blinded to treatment conditions evaluated the images according to the qualitative score previously described.…”
Section: Histopathological Analysismentioning
confidence: 99%
“…This study has several limitations. Because repeated intramuscular injection of local anesthetics results in myotoxicity (49,50), this study used a short-term intervention, 2 weeks of treatment, to compare the effects of SM and TPI treatment. Although prior investigations reported that weekly TPI for 1-2 weeks immediately improved myofascial pain (16)(17)(18)40,51), some studies noted significant decreases in pain scores over 4 weeks after repeated TPI for MTrPs in patients with myofascial pain (43,52,53).…”
Section: Discussionmentioning
confidence: 99%